In deep waters : spiritual care for young people in a climate crisis - Aho, Talitha Amadea (Fortress Press, 2022)
"The starting point for In Deep Water: Spiritual Care for Young People in a Climate Crisis is not news: the world as we know it is shifting. Several millennia of climate stability have come to an abrupt end.But, observes Talitha Amadea Aho, the young people of today do not remember stability. They see the world through crisis-colored glasses. Climate change is creating a spiritual emergency that is hitting their generation harder than any other. We must learn how to offer spiritual care that is informed by the spiritual-ecological crisis of this time. This book will help you keep young people at the center of your community and listen to the troubles they have to share. Whether you are a Gen Z peer or a caring adult of any other generation, In Deep Water will show you how to offer ecologically informed spiritual care."--Publisher.